Multiscale estimation of ageing viscoelastic properties of cement-based materials: A combined analytical and numerical approach to estimate the behaviour at early age. (July 2016) - Honorio, Tulio; Bary, Benoit; Benboudjema, Farid
Abstract: We propose an investigation combining numerical and analytical tools to estimate the ageing viscoelastic properties of cement-based materials within a multiscale framework. With analytical homogenization the properties at the cement paste and mortar scales are estimated by a combination of Generalized Self-Consistent (GSC) and Mori–Tanaka (MT) schemes. With numerical homogenization the effective properties at the concrete scale are estimated. Numerical homogenization has the advantage of allowing assessing local information and to study more complex geometries. This combined strategy constitutes a promising tool to investigate how different mechanisms leading to ageing at the hydrated products scale, as well as other features of cement-based materials such as the Interfacial Transition Zone (ITZ), affect the viscoelastic behaviour at superior scales. In this context, we study the solidification of non-ageing constituents as the mechanisms leading to the ageing behaviour combined or not with a space-filling process in C–S–H. Relaxation and creep results are presented.